Use of Dispersive Liquid-Liquid Microextraction and UV-Vis Spectrophotometry for the Determination of Cadmium in Water Samples - J. Pérez-Outeiral; E. Millán; R. Garcia-Arrona (Journal of Spectroscopy)
A simple and inexpensive method for cadmium determination in water using dispersive liquid-liquid microextraction and ultraviolet-visible spectrophotometry was developed. In order to obtain the best experimental conditions, experimental design was applied. Calibration was made in the range of 10–100 μg/L, obtaining good linearity (R2 = 0.9947). The obtained limit of detection based on calibration curve was 8.5 μg/L. Intra- and interday repeatability were checked at two levels, obtaining relative standard deviation values from 9.0 to 13.3%. The enrichment factor had a value of 73. Metal interferences were also checked and tolerable limits were evaluated. Finally, the method was applied to cadmium determination in real spiked water samples. Therefore, the method showed potential applicability for cadmium determination in highly contaminated liquid samples.